2011
DOI: 10.1136/hrt.2011.227652
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analyses of the association between cytochrome CYP2C19 loss- and gain-of-function polymorphisms and cardiovascular outcomes in patients with coronary artery disease treated with clopidogrel

Abstract: Not only CYP2C19 loss-of-function but also gain-of-function alleles should be considered to define the pharmacogenetic response to clopidogrel. The results question the relevance of the CYP2C19 loss-of-function alleles in the prediction of major cardiovascular events beyond stent thrombosis in coronary patients treated with clopidogrel. The gain-of-function variant is associated with a lower risk of cardiovascular events but a higher risk of bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
132
3
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 144 publications
(140 citation statements)
references
References 45 publications
3
132
3
2
Order By: Relevance
“…Six meta-analyses reduced heterogeneity by excluding one or more studies, 5,8,[24][25][26]29 and four of these found that the resulting pooled effect estimate remained unchanged. 5,8,24,26 Five meta-analyses performed stratified meta-analyses by study and population characteristics, 7,8,25,26,29 two performed metaregression, 5,20 and one inspected primary study characteristics. 5 Higher sample size and poorer quality of the primary studies were associated with lower effect sizes, 7,25 but other studies did not find an impact of study characteristics.…”
Section: Heterogeneitymentioning
confidence: 99%
See 4 more Smart Citations
“…Six meta-analyses reduced heterogeneity by excluding one or more studies, 5,8,[24][25][26]29 and four of these found that the resulting pooled effect estimate remained unchanged. 5,8,24,26 Five meta-analyses performed stratified meta-analyses by study and population characteristics, 7,8,25,26,29 two performed metaregression, 5,20 and one inspected primary study characteristics. 5 Higher sample size and poorer quality of the primary studies were associated with lower effect sizes, 7,25 but other studies did not find an impact of study characteristics.…”
Section: Heterogeneitymentioning
confidence: 99%
“…Five of these eight concluded that there was an association between CYP2C19 loss-of-function alleles and the clinical end point, 24,26-29 two inferred that there was a possible association, 7,8 whereas one concluded that the association was not proven because of publication bias ( Table 2; Supplementary Table S4 and Supplementary Appendix S1 online). 6 The remaining three meta-analyses found no statistically significant pooled effect 5,25 or did not pool the data because of between-study heterogeneity. 30 Of the four meta-analyses that concluded absence of association, three were among the five most recently published.…”
Section: -82426-29mentioning
confidence: 99%
See 3 more Smart Citations